1992
DOI: 10.20506/rst.11.4.648
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophilosis in camels (Camelus dromedarius Linnaeus, 1758) in Kenya

Abstract: Natural dermatophilosis (caused by Dermatophilus congolensis Van Saceghem, 1915) has only recently been described in camels (Camelus dromedarius). Further work has shown that the disease is actually widespread. At the Ol Maisor farm where it was first diagnosed (in the Laikipia district of northern Kenya), detailed investigations have revealed that thirty camels (ten calves and twenty adult animals) were infected. The signs varied from mild to more than 50% skin involvement. Patches of wool on the rump were ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…The disease usually affects camels 1-3 years of age, and the incubation period may extend up to 3 months. In the current study, the prevalence of dermatophilosis was significantly higher in young camels (1-4 years of age) compared to camels ≥ 5 years of age (p < 0.05), which is similar to the findings of other reports [14,16]. D. congolensis may be isolated in pure culture from clinical materials by streaking scabs or exudate, preferably from unopened pustules, directly to blood agar plates, and incubating aerobically in the presence of 5% CO 2 at 37°C for 48 hours.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The disease usually affects camels 1-3 years of age, and the incubation period may extend up to 3 months. In the current study, the prevalence of dermatophilosis was significantly higher in young camels (1-4 years of age) compared to camels ≥ 5 years of age (p < 0.05), which is similar to the findings of other reports [14,16]. D. congolensis may be isolated in pure culture from clinical materials by streaking scabs or exudate, preferably from unopened pustules, directly to blood agar plates, and incubating aerobically in the presence of 5% CO 2 at 37°C for 48 hours.…”
Section: Discussionsupporting
confidence: 92%
“…In camels, a mixed infection of D. congolensis and Microsporum gypseum has been reported [12]. Experimental infection with D. congolensis isolated from cattle has been described in camels, cattle, goats, sheep, donkeys, and rabbits [13,14]. Transmission follows the disruption of the natural skin barriers by skin abrasions from thorns, grain awns, ticks, and flies.…”
Section: Introductionmentioning
confidence: 99%
“…Dermatophilosis has been described in dromedary camels in Kenya (Gitao et al 1990;Gitao 1992). They reported that the disease was more prevalent in the wet season (21.2%) compared with its prevalence in the dry season (14.5%), and the calves were found to be more susceptible (23.1%) compared with the adults (19%).…”
Section: Discussionmentioning
confidence: 99%
“…More than 200,000 dromedary camels are living in the arid and semiarid deserts of Iran (Rahbari and Bazargani 1995;Mowlavi et al 1997). In camels, dermatophilosis has been reported in Kenya, Sudan, and Saudi Arabia (Gitao et al 1998a(Gitao et al , b, 1990Gitao 1992), but has not been previously reported in Iran. Therefore, the present study describes the prevalence, pathogenesis, and gross and histopathologic lesions of this disease in the camels of the central part of Iran.…”
Section: Introductionmentioning
confidence: 96%
“…The skin scabs were emulsified in phosphate buffered saline (pH 7.2) and inoculated onto sheep blood agar as described previously. 2 Processing for histopathological staining with Giemsa, Hematoxilin/eosin and PAS was also performed as described earlier. 2 Disc slide antibiotic sensitivity was tested by emulsifying a loopfull of the organism from SBA in PBS between two slides.…”
Section: Methodsmentioning
confidence: 99%